2015
DOI: 10.5897/jphe2014.0679
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of factors associated with neonatal length of stay in Sunyani, Ghana

Abstract: Postpartum length of stay (LOS) in hospital continues to be a subject of intense discourse and research, especially for mothers of neonates born with low birth weight (LBW). This study investigates the association of total LOS (pre and postpartum) with a range of factors related to geo-demographics, maternal health and pregnancy history. It also provides simple estimates of likely duration of neonatal hospital length of stay based on data from two public hospitals at Sunyani, Brong Ahafo Region, Ghana. The LOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
2
1
2
Order By: Relevance
“…The results from the 2017 cohort rather revealed that women at their advanced maternal age 30+ years were 1.24 times more likely to have prolonged length of hospitalization after vagina delivery than women aged 15-19 years. This finding was consistent with other earlier published studies [11,33]. Van otterloo et al found women aged above 30 years were at 1.49-1.77 times higher risk of prolonged length of stay after both vaginal and cesarean births than those aged 25-29 years [33].…”
Section: Plos Global Public Healthsupporting
confidence: 93%
See 2 more Smart Citations
“…The results from the 2017 cohort rather revealed that women at their advanced maternal age 30+ years were 1.24 times more likely to have prolonged length of hospitalization after vagina delivery than women aged 15-19 years. This finding was consistent with other earlier published studies [11,33]. Van otterloo et al found women aged above 30 years were at 1.49-1.77 times higher risk of prolonged length of stay after both vaginal and cesarean births than those aged 25-29 years [33].…”
Section: Plos Global Public Healthsupporting
confidence: 93%
“…Advanced maternal age has been identified as a significant determinant of most pregnancy discharge outcomes, which prolonged hospitalization is not an exception [11,32,33]. The present study's results on the 2007 cohort found no significant association between all age groups and prolonged hospitalization after vaginal delivery.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…La presente investigación arroja evidencia que demuestra que la edad de la madre es un determinante de estancias prologadas en rn. Se observa que los hijos de madres jóvenes (>18 años) y mayores (<34 años) son los que tienen mayor probabilidad de ingresar a uci y generar estancia prolongada (8,22,27). Por otro lado, contar con al menos un control prenatal disminuye la probabilidad de que un neonato genere estancias prolongadas.…”
Section: Discussionunclassified
“…Es importante mencio-nar que el hacinamiento, no contar con servicio de gas y la exposición a basuras resultaron no significativas. Sin embargo, diversos estudios han identificado que componentes como necesidades básicas insatisfechas (estrato socioeconómico), familias monoparentales (madre sola), ubicación geográfica, entre otros impactan significativamente en la duración del neonato en uci (26,27).…”
Section: Discussionunclassified